Analysis and Design of Susuka Hotel's Ordering and Payment Information System Using the Waterfall Method - Zahara; Dori Gusti Alex Candra; Eka Sofiati; Atika Fauziyyah; Jufri Jufri (Yayasan Insan Mulia Bima, 2025)
The reservation and payment information system at Susuka Hotel is an essential requirement to support operational efficiency and effectiveness. This study aims to analyze and design an information system that facilitates a faster and more convenient reservation and payment process, thereby improving customer service quality. The method used in this study is the Waterfall method, which consists of several stages: requirements analysis, system design, implementation, testing, and maintenance. During the analysis stage, data were collected through interviews and observations to understand the needs of the hotel and its customers. The system design results include the development of a user interface, database structure, and workflow for the reservation and payment processes. With the implementation of this system, Susuka Hotel is expected to enhance operational efficiency, reduce manual errors, and provide a better experience for customers. This information system is implemented using web-based programming to enable real-time access and ease of use.